(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2023)
With increasing demand for renewable energy resources, the development of alternative concepts is still ongoing. The wave energy sector is still in vast develop- ment on the way to contribute to the energy production world wide. The present study presents the development of the Exowave wave energy converter made so far. A numerical model has been established supported by wave flume tests performed at Aalborg University during the first phase of the development. Furthermore, a successful open sea demonstration has been performed on 7 meters of water at Blue Accelerator, Belgium, from which the concept has been proven. As part of the ongoing research, verification of the numerical model will be made through experimental testing in the wave tank of Aalborg University, and an open sea demonstration at 14 meters of water depth will be executed off the coast of Hanstholm, Denmark.